THE EFFECT OF LEADERSHIP AND ORGANISATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATING VARIABLE - Andrian Syahrul Permana; Sri Padmantyo (Universitas Maarif Hasyim Latif, 2023)
The purpose of this study is to explain the influence of leadership and organizational culture on employee performance with job satisfaction as a mediating variable. This research uses a type of quantitative research using primary data obtained from the results of distributing questionnaires via Google form with a Likert scale toemployees of PT. Oemah Insan Mandiri. The sampling technique in this study is non-probability sampling. The number of samples in this study is 135 respondents. The data analysis technique in this study uses Partial Least Square (PLS) with the help of SMARTPLS Software. PLS-SEM analysis consists of two, namely the Outer model andInner model. The results showed a positive and significant influence of leadership and organizational culture on employee performance with job satisfaction as a mediating variable